Identifying the level of virtual tourism technology knowledge of tourism awareness groups in the City of Padang - Alhapen Ruslin Chandra; Afifah Afifah; Alfatah Haries; Rafidola Mareta Riesa; Tuti Azra (Jurnal Pariwisata Pesona, 2023)
Virtual tour is a tourism activity that is carried out through web browsing using media such as images or videos to provide users with the feeling of being in the tourist destination. This activity can also be used as a means to promote tourist attractions. One group that is expected to adopt this virtual tour technology is Kelompok Sadar Wisata (Pokdarwis), as this group has a role in promoting local tourist attractions.  Virtual tour is a relatively low-cost promotional tool compared to other promotional media, yet with a wider reach of audience. This research aims to identify the understanding and ability of Pokdarwis Padang City related to the acceptance of virtual tour technology. This study was conducted through questionnaires involving 48 leaders and members of Pokdarwis of Padang City, where technical knowledge, ease of use, and perception of the benefits of virtual tour formed the basis of the questions. Descriptive analysis results show that the majority of Pokdarwis members lack of adequate knowledge of virtual tour and the appropriate use of technology in creating virtual tour. On the other hand, Pokdarwis members are already able to use social media but lack of adequate technical skills in creating virtual tour content.